ANALISIS STRATEGI PEMASARAN KREDIT, PROSEDUR PEMBERIAN KREDIT, DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH KOPERASI SIMPAN PINJAM - Bambang Riono, Slamet (Lembaga Pengembangan Kinerja Dosen, 2022)
Customer satisfaction is an important element as a determinant of the success of a business entity in meeting the needs and expectations of the community. The effect of customer dissatisfaction and disloyalty to a product or service depends on the service provided. The purpose of this study was to identify and analyze credit marketing strategies, procedures for granting credit, and service quality to customer satisfaction at the Dhuafa Savings and Loans Cooperative Office (Komida). The type of research used is field research, namely by looking for data directly in the field. This research was conducted at the Komida Wiradesa Branch Office. Sources of data in this study using primary data derived from the results of respondents' answers to research instruments in the form of a set of questionnaires given to customers. In this study, the population is all customers who have applied for credit, amounting to 2,577 people. Furthermore, the number of samples obtained was 96 respondents. The analysis used in conducting the research is quantitative descriptive analysis by describing the data obtained from filling out the questionnaires that have been carried out and then easy to understand and then draw conclusions. The results of the study indicate that the credit marketing strategy has an effect on customer satisfaction; the procedure of giving credit has an effect on customer satisfaction; and service quality affect customer satisfaction. Based on the results of the multiple regression equation obtained Y = (12,554) + 0.317X1 + 0.234X2 + 0.176X3 + e. It means that the constant value (α) is positive at 12,554, meaning that there is a unidirectional effect between the independent variable and the dependent variable. The result of the coefficient of determination (Adjusted R Square) is 0.436. This means that the contribution of the Credit Marketing Strategy (X1), Credit Provisioning Procedure (X2), and Service Quality (X3) variable contribution to Customer Satisfaction (Y) is 43.60%, while the remaining 56.40% is explained by other variables that are not revealed in this study.